(untitled) (Journal of Pedagogical Inventions and Practices, 2022)
At the current stage of development of the society, in the field of physical culture and sports, issues related to the development of motor skills and management of the level of physical fitness of students in general secondary schools are of particular importance. The educational process in general secondary schools involves the creation of the basics of basic physical training, the formation of the necessary fund of motor skills and abilities in students, their harmonious development in all respects. However, it has been observed that the level of manifestation of basic movement qualities in schoolchildren does not meet today’s requirements